Atuação do psicólogo escolar junto a professores da educação básica: concepções e práticas - Nascimento, Ana Rogélia Duarte do (2020)
This research analyzed the conceptions and practices of school psychologists and teachers about the role of the school psychologist alongside teachers in monitoring the teaching and learning process. Critical-basis studies in the field of school psychology point out the importance of the work of psychologists with teachers mediating the teacher-student relationship, to promote and enhance the learning and development processes, a relevance addressed even in technical documents to guide the work of psychologists in Basic Education. The theoretical framework that underlies this research is the historical-cultural theory, which explains the relationship between learning and human development, and how the teaching and learning processes collaborate for the formation of scientific concepts that the subjects appropriate from their insertion in school. In this sense, a qualitative research was conducted, with seventeen school psychologists, sixteen elementary school teachers, and sixteen elementary school teachers from public schools in the city of João Pessoa-PB. To analyze the participants' conceptions and practices, two semi-structured interview scripts and two sociodemographic questionnaires were used, directed to each group. The interviews were recorded in audio and transcribed in full for analysis, according to the guidelines of the content categorization method presented by Bardin (2000). The results allowed us to realize that the actions of the psychologists had a collective character, with interventions more focused on the faculty and other professionals of the institution than specific actions with students and their families. Regarding the teacher's monitoring of the teaching and learning process, it was not explained by the psychologists how these actions occurred and how they contributed to the teaching and learning process and pedagogical practice. Part of the psychologists said they carried out training activities with the faculty, as well as carrying out preventive work. It was found that the teachers of both segments comprise, in their majority, the role of the psychologist still associated with emergency issues and individual assistance with students and their families. For the teachers, the possibilities of intervention by psychologists would be training activities, guidance, and reflection on pedagogical practice. The results also demonstrated that, in the view of psychologists, the situations that teachers consider interfering in the teaching and learning process were the students' problems/difficulties. For the teachers of the first segment of elementary school, it was the absence of family monitoring in the school life of the students, and for the teachers (s) of the second segment of elementary school, it was the deficit in the school and resource structure. The analysis of these results allows us to defend the plausibility of the work of psychologists with teachers in order to establish a partnership with this professional, as well as being an important indicator for proposing interventions with the faculty, based on a preventive, psychosocial, and institutional perspective. It also warns of the importance of psychologists in the context of education to continually appropriate theoretical and methodological assumptions to act in a critical, conscious and transformative way, in order to mobilize the concepts and practices of other school actors about their importance in education and human development.